Animating the excretory system: An interactive learning tool for eighth grade students - Susanti, Baiq Hana; Safitri, Novita Dwi; Listanto, Virgiawan; Permatasari, Anggraeni Dian (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2023)
In Biology class, students face problems understanding the material that seems abstract to observe, such as biological system mechanisms. This study was aimed at developing interactive learning media products based on animated videos using the Unity application in the excretory system lesson for eighth grade and determine the response of teachers and students. This study adapted the ADDIE model to develop interactive learning media. The steps in this study are analysis, design, development, implementation, and evaluation. The findings indicate that the content quality and media quality percentages are 83.35% (very feasible category) and 92.75% (very viable category) respectively. Furthermore, students scored the product in average 84.5% (very feasible category). Meanwhile, the science teachers assessed the product in average 91.7% (very viable category) from the teachers. The results of the Wilcoxon signed-rank test also showed a significant difference between the students' pretest and posttest results. It can be concluded that the interactive learning media based on animated videos can be used as an alternative learning media in the excretory system lesson for eighth grade students.